The Salut les copains generation. Issue 3 (December 2020) - Morin, Edgar; Hawkins, Peter; Lebrun, Barbara
Abstract : In Paris on 22 June 1963, the French youth magazine Salut les copains celebrated its first year in print by organising a free outdoor concert on the Place de la Nation. The artists headlining the gig were young male and female pop singers who had been propelled to the top of the French charts thanks to the regular broadcasting of their music on the show Salut les copains (on private radio station Europe 1 since 1959), and extensive coverage in the weekly magazine of the same name (since 1962). The 150, 000-strong crowd at the concert exceeded all expectations, but also generated a sense of moral panic in the media as worried commentators speculated on the dangerous mindlessness of such 'rhythmic' music for impressionable French youngsters.